From school to home: Understanding the experiences of parents and learners in modular learning - Joel B. Lopez; Anni D. Pagdilao; Eldefonso B. Natividad, Jr; Opresinia Z. Castillo; Aileen B. Joaquin; Aubrhey Marie R. Oasay, (Divine Word International Journal of Management and Humanities (DWIJMH) (ISSN: 2980-4817), 2023)
The emergence of the COVID-19 pandemic brought a major shift in the delivery of instruction. Parents and learners were caught unprepared for this situation. As such, this study aimed to describe the experiences of parents and learners in modular learning. Following a phenomenological approach, 10 parents and 30 learners from the Schools Division of the City of Batac underwent unstructured interviews via home visits, phone calls, and messenger calls. It adopted the Hycner transcription analysis methodology for the data analysis. Findings revealed that parents’ experiences could be described along four themes: multiple roles, learning management challenges, home learning strategies, and support systems. Meanwhile, learners’ experiences were revealed by these four themes: learning preferences, learning struggles, learning strategies, and learning support. Interestingly, these experiences magnify the need for attention to shared responsibility, understanding, cooperation, commitment, and compassion for modular learning to succeed in the context of a pandemic. Furthermore, the findings could serve as a basis for providing comprehensive and inclusive educational policies that facilitate the adjustments of learners and parents in a new learning setup. As such, schools can create and implement more adoptive, relevant, and inclusive institutional plans, projects, activities, and programs for the attainment of optimum learning gains.